2021
DOI: 10.1002/ece3.7871
|View full text |Cite
|
Sign up to set email alerts
|

High functional diversity in deep‐sea fish communities and increasing intraspecific trait variation with increasing latitude

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 94 publications
2
14
0
Order By: Relevance
“…To measure the divergence and the regularity dimensions we worked directly with the Gower distance matrix to avoid loss of information associated with the dimensionality reduction by the PCoA. For the divergence dimension, we calculated the Mean Pairwise Functional Distance index (MPFD) corresponding to the mean functional distance between all species pairs (Myers et al, 2021). Finally, we measured functional regularity with the Variance in Pairwise Functional Distance (VPFD) index, quantifying the regularity of the functional distances among species (Myers et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To measure the divergence and the regularity dimensions we worked directly with the Gower distance matrix to avoid loss of information associated with the dimensionality reduction by the PCoA. For the divergence dimension, we calculated the Mean Pairwise Functional Distance index (MPFD) corresponding to the mean functional distance between all species pairs (Myers et al, 2021). Finally, we measured functional regularity with the Variance in Pairwise Functional Distance (VPFD) index, quantifying the regularity of the functional distances among species (Myers et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…For the divergence dimension, we calculated the Mean Pairwise Functional Distance index (MPFD) corresponding to the mean functional distance between all species pairs (Myers et al, 2021). Finally, we measured functional regularity with the Variance in Pairwise Functional Distance (VPFD) index, quantifying the regularity of the functional distances among species (Myers et al, 2021). We then decorrelated the different functional metrics from SR by computing their Standardized Effect Size (SES) values.…”
Section: Functional Traits Collection and Functional Index Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen raw morphological measurements were obtained from individuals of each species of fish, in situ , by reviewing footage obtained from each Stereo‐BRUV deployment and using the software ‘EventMeasure’ (http://www.seagis.com.au; see Myers et al . (2021) and Appendix : Table S1). Where possible, measurements from multiple individuals of a single species within a given depth‐by‐location cell were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study suggested that the functional alpha diversity for fishes (based on their morphological traits) remains relatively stable to a depth of ˜1200 m, while functional distances among individuals within communities increases with depth (Myers et al . 2021). These results run counter to the classical ecological paradigm that functions are filtered more strongly in harsh environments than in benign environments (Swenson et al .…”
Section: Introductionmentioning
confidence: 99%